When they win, you win being a great manager is simpler than you think - Laraway, Russ. (New York St. Martin's Press, 2022)
In When They Win, You Win, Russ Laraway, the Chief People Officer of Goodwater Capital, provides a simple, coherent, and complete leadership standard that teaches organizational planners and managers how to develop incredible levels of employee engagement. The book identifies three key elements: clear direction-setting, frequent coaching, and active engagement with employees on their long-term career goals.
Keywords: Management